Analisis Sentimen Pada Komentar Mengenai Kartu Indonesia Pintar Menggunakan Metode Naïve Bayes - Dava Sindy; Sriani Sriani (JURIKOM (Jurnal Riset Komputer), 2025)
The Indonesia Smart Card (Kartu Indonesia Pintar – KIP) is a government program aimed at providing educational assistance to students from underprivileged families. This program seeks to improve access to education and increase learning opportunities for children, enabling them to complete their education up to the secondary or vocational level. In the digital era, public opinion regarding government policies, including KIP, is often expressed through social media platforms such as X. Sentiment analysis is a technique in natural language processing (NLP) used to identify, extract, and classify opinions from text. One of the commonly used algorithms for sentiment analysis is Naïve Bayes, which operates based on Bayes' Theorem with the assumption of feature independence. This algorithm is effective in text classification due to its simplicity and ability to handle large datasets.By utilizing the Naïve Bayes algorithm, sentiment analysis of the KIP program can provide deep insights into public responses. The results of this analysis can assist the government in evaluating policies, understanding public perceptions, and optimizing program implementation to ensure it effectively reaches its intended beneficiaries.